Directing Group Assisted Copper‐Catalyzed C−H sulfanylation of Alkenyl Carbonyl Compounds with Disulfides - Bai, Yan‐Mei; Ai, Lu‐Lu; Zhang, Xin‐Mei; Wu, Fang‐Hui; Kang, Yan‐Shang (European journal of organic chemistry, 2024)
A highly efficient and straightforward copper‐catalyzed sulfanylation of acrylamides with readily available disulfides has been developed. Through 8‐aminoquinoline‐assisted activation of the alkenyl C−H bond, a broad scope of (Z)‐alkenyl sulfides were constructed in moderate to excellent yields with good compatibility of functional groups. Moreover, the bidentate directing auxiliary promotes high regioselectivity of (Z)‐β‐alkenyl sulfides, and enables the excellent performance of copper catalyst in this transformation. In this paper, a highly efficient copper‐catalyzed sulfanylation of alkenyl carbonyl compounds with readily available disulfides has been developed. The bidentate directing auxiliary has been demonstrated to promote the activity of copper catalyst under mild oxidizing conditions, prevents copper catalyst deactivation in the catalytic cycle, and ensures high regioselectivity of (Z)‐β‐alkenyl sulfides in this transformation.